Investigation of Herb-Drug Interactions between Xylopia aethiopica, Its Principal Constituent Xylopic Acid, and Antidepressants - Christian C. Ndu; Wonder K. M. Abotsi; Priscilla K. Mante (Hindawi Limited, 2024)
Introduction. Depression affects an estimated 350 million people worldwide and is implicated in up to 60% of suicides. Only about 60-70% of patients respond to antidepressant therapy. One of the factors causing patients to not attain therapeutic goals is herb-drug interactions. Objective. To investigate any potential herb-drug interaction that might exist between Xylopia aethiopica extract (XAE) or xylopic acid (XA) and selected conventional antidepressants (imipramine, fluoxetine, and venlafaxine) in mice. Methods. Dried, powdered fruits of Xylopia aethiopica were cold macerated in 70% ethanol to obtain XAE. XA was isolated by cold macerating dried fruits of Xylopia aethiopica in petroleum ether, crystallising impure XA with ethyl acetate, and purifying XA crystals with 96% ethanol. Pharmacodynamic interaction was assessed via isobolographic analysis of tail suspension tests of the agents individually and in their respective combinations. Pharmacokinetic interaction was assessed by monitoring the effect of coadministrations on the plasma concentration of antidepressants and xylopic acid via HPLC analysis. Results. XAE and XA in mice showed significant antidepressant-like activity in the tail suspension test. With interaction indices less than one, synergism of antidepressant effect was observed in the Xylopia aethiopica extract/fluoxetine (γXAE/FL = 0.502), Xylopia aethiopica extract/imipramine (γXAE/IP = 0.322), Xylopia aethiopica extract/venlafaxine (γXAE/VL = 0.601), xylopic acid/imipramine (γXA/IP = 0.556), xylopic acid/venlafaxine (γXA/VL = 0.451), and xylopic acid/fluoxetine (γXA/FL = 0.298) combinations, which may be potentially due to elevation of serotonergic neurotransmission via varying mechanisms. The AUC of imipramine (AUCIP = 1966 ± 58.98 µg/ml.h) was significantly (P<0.0001) reduced by Xylopia aethiopica extract (AUCIP = 1228 ± 67.40 µg/ml.h) and xylopic acid (AUCIP = 1250 ± 55.95 µg/ml.h), while the AUC of xylopic acid (AUCXA = 968.10 ± 61.22 µg/ml.h) was significantly (P<0.0001) reduced by venlafaxine (AUCXA = 285.90 ± 51.92 µg/ml.h) and fluoxetine (AUCXA = 510.60 ± 44.74 µg/ml.h), possibly due to the effect of interfering agents on gastric emptying hence reducing oral absorption. Conclusion. Xylopia aethiopica extract and xylopic acid interacted synergistically with imipramine, fluoxetine, and venlafaxine and reduced the systemic circulation of imipramine.